Konstruksi Laporan Keuangan Bumdes Berdasarkan Peraturan Daerah No 09 Tahun 2013 Mengenai Pengelolaan Bumdes di kecamatan Palang Kabupaten Tuban - Adi Supeno; Dewi Sutjahyani (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Determination of Law Number 23 of 2014 concerning Regional Government, (State Gazette of the Republic of Indonesia of 2014 Number 244, Supplement to State Gazette of the Republic of Indonesia Number 5587) in which several provisions in Law Number 23 of 2014 concerning Regional Government have been amended by Government Regulations In lieu of Law (PERPPU) Number 2 of 2014 concerning Amendments to Law Number 23 of 2014 concerning Regional Government, has automatically replaced Law Number 32 of 2004. The research carried out by the author uses a descriptive qualitative research approach, in particular by adopting the case study method. The focus of this research is to reveal information related to the research object with the aim of measuring its level of effectiveness. Based on the results of observations made by researchers, there are findings obtained from the Management of BUMDES Bahari Makmur, starting from reporting, management, information and communication, BUMDES activities, namely: Condition: there is no Good and Correct Financial Reporting, including Financial Reporting According to Regional Regulations No. 09 of 2013, there is no BUMDES organizational structure. Cause: lack of village government involvement, where BUMDES itself is an increase in the village budget. Consequence: BUMDES Bahari Makmur is not functioning as BUMDES is a Village Institution that must exist. 1. It is hoped that the Palang Village government should improve BUMDES reporting and reactivate BUMDES so that the village can get original income. This is important because BUMDES itself is mandatory. 2. It is hoped that the Palang village government can provide information about financial reporting and BUMDES management so that readers can get information about BUMDES management. 3. It is hoped that future researchers will be able to explore in more detail and expand the BUMDES financial management process with Regional Regulation Number 09 of 2013, because in this research it is limited to management and reporting, not access to financial reporting and BUMDES management.